Photodynamic therapy in the treatment of non-melanoma skin cancer: A literature review (International Seven Journal of Multidisciplinary, 2024)
Objective: The following study aims to analyze the mechanism of action, efficacy, safety and recent trends in the use of photodynamic therapy (PDT) as a therapeutic approach in the treatment of non-melanoma skin cancer. In addition, it seeks to provide a comprehensive overview of the current state of knowledge on the subject, highlighting its use and availability in the Brazilian scenario. Methods: The research was carried out using a literature review based on data published in Periódicos CAPES, Biblioteca Virtual de Saúde (BVS) and UpToDate. Results: PDT is a technique that has already been consolidated globally and has several advantages in the treatment of non-melanoma skin cancer, as well as actinic keratoses, even in comprehensive cases. PDT is considered a non-invasive, fast, safe method, with few side effects, providing rapid recovery and being well tolerated by patients. It has a significant cure rate and excellent aesthetic results, differing from other treatments often cited for their disadvantages, such as undesirable scars. Conclusion: It is crucial to further explore the benefits of PDT, considering its application in different subtypes of non-melanoma skin cancer and optimizing protocols to expand its clinical application. As a promising innovation, the technology has the prospect of contributing to improving the quality of life of patients affected by this specific type of skin cancer.